A Case Study of How Natural Phenomena Were Justified in Medieval Science: The Situation of Annular Eclipses in Medieval Astronomy. Issue 1 (6th February 2014) - Mozaffari, S. Mohammad
Argument The present paper is an attempt to understand how medieval astronomers working within the Ptolemaic astronomical context in which the annular eclipse is an unjustified and impossible phenomenon, could know, define, justify, and later make attempts that led to success in predicting annular solar eclipses. As a context-based study, it reviews the situation of annular eclipses with regard to the medieval hypotheses applied to the calculation of the angular diameters of the sun and the moon, which was basic for contemplating the possibility of annular eclipses. This gives the premises and the preliminary insights that were necessary to clarify the complex situation of the annular eclipse in the late medieval Islamic period and to explain the historical mechanisms leading to justifying the phenomenon during that period. This was, first due to a convincing and efficient observational evidence which, of course, was available only to a number of medieval astronomers and significantly for only a limited time period, and, second, the result of an amazing interaction amongst various astronomical traditions available to them. At a more general level, the research aims to inspect or, at least, to give some impressions of the essential conditions, i.e., identification of phenomenon, empirical evidence, and the justifying underlying tradition, under which it became possible in the tradition-based science of the `medieval period to permit a not-already-defined and tradition-opposed phenomenon to be posed and justified.